Development of cottage cheese from a blend on non-fat dry milk and cocopro 1 - Escalona, Nimphanida V.
The possibility of utilizing cocopro 1, a dehydrated coconut by-product, in making cottage cheese was explored. Two methods of cheese coagulations, renner and vinegar coagulations, were employed. The levels of cocopro 1 replacing NFDM for rennet curdling were 15%, 25% and 35%. A sudden drop in yield occurred in cheese when 35% of NFDM was replaced by cocopro 1 and acceptability became low. Percentage protein of all coagulated cottage cheese were relatively, 17.4% - 21.3%. As more cocopro 1 was used, production became a problem because weak curds appeared. The levels of cocopro 1 replacing NFDM using vinegar coagulation were 10%, 15%, 20%, 25%, 45% and 55%. Vinegar coagulation resulted to more or less constant yield, satisfactory acceptability and high percentage protein content for all samples. Acceptability went down only at 55% replacement of NFDM. With these levels of cocopro 1, protein content of cheese samples ranged from 15.5% to 25.3%. Generally, as more cocopro 1 was used, the curd became finer and fragile. Production problems were incurred in cheese samples with 45% and 55% replacement of NFDM by cocopro 1.